Criminal law - Binder, Guyora (New York, NY : Oxford University Press, 2016)
In 'Criminal Law', Guyora Binder reviews the development of American criminal law and explains its key concepts and persistent controversies in light of that history.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 15, 2016).
Keywords: Criminal law -- United States; Law